(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
The influence of the main technological parameters and the content of modifiers and plasticizers on the physical and mechanical properties of non-woven thermally bonded materials has been studied. The optimal values for the content of binder, plasticizer, modifier, catalyst and thermal bonding conditions have been established